2009
DOI: 10.1017/s1047951109990795
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 improves diastolic function in children with idiopathic dilated cardiomyopathy

Abstract: We aimed to determine the effect of supplementation with coenzyme Q10 on conventional therapy of children with cardiac failure due to idiopathic dilated cardiomyopathy. In a prospective, randomized, double-blinded, placebo-controlled trial, we randomized 38 patients younger than 18 years with idiopathic dilated cardiomyopathy to receive either coenzyme Q10, chosen for 17 patients, or placebo, administered in the remaining 21. Echocardiographic systolic and diastolic function parameters were determined for ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…[8][9][10] It has also been reported that CoQ 10 has a hypotensive effect. 7,11,12) In addition, a number of people who usually intake CoQ 10 as a supplement also receive some kinds of drugs to treat high blood pressure.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…[8][9][10] It has also been reported that CoQ 10 has a hypotensive effect. 7,11,12) In addition, a number of people who usually intake CoQ 10 as a supplement also receive some kinds of drugs to treat high blood pressure.…”
Section: Introductionmentioning
confidence: 95%
“…CoQ 10 is a fat-soluble, vitamin-like benzoquinone compound that functions primarily as an antioxidant, a membrane stabilizer, and a cofactor in the oxidative phosphorylation process that leads to the production of adenosine triphosphate (ATP) in its reduced form. [1][2][3] CoQ 10 is widely consumed as a food supplement because of its status as an important nutrient for maintaining human health. The rationale for the use of CoQ 10 as a medical agent for treating cardiovascular diseases is based on its fundamental role in mitochondrial function and cellular bioenergetics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CoQ10 has been reported to have beneficial effects on the heart, lungs, liver, and skin. 1,2 It has been shown that by lowering matrix metalloproteinase levels in fibroblasts, CoQ10 reduces wrinkles. 3 CoQ10 also exerts anti-inflammatory effects on dermal fibroblasts.…”
Section: Introductionmentioning
confidence: 99%